2021
DOI: 10.1097/hs9.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Constitutional Mismatch Repair Deficiency in a Pediatric T-cell Lymphoblastic Lymphoma Cohort

Abstract: This study describes the clinical characteristics of a complete Dutch T-cell lymphoblastic lymphoma (T-LBL) cohort, including second primary malignancies and comorbidities. We show that over 10% of patients in this complete T-LBL cohort have been diagnosed with a cancer predisposition syndrome (CPS), consisting almost exclusively of constitutional mismatch repair deficiency (CMMRD). The clinical characteristics of sporadic T-LBL patients were compared with T-LBL patients that have been diagnosed with CMMRD. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The 2/19 (10.5%, 95% CI: 1.3-33.1%) relapse samples that were MMR deficient in this study is also consistent with the reported 4-10% frequency. Recently, the TP53 variant c.743G>A (p.R248Q) was found to associate with concurrent MMR deficiency and thiopurine treatment [12], but this variant was [1], and 8/88 (9.1%, 95% CI: 0.4-17.1%) childhood T-LBL patients were diagnosed with CMMRD in a consecutive series between 2007 and 2020 [13], suggesting an association of CMMRD with T cell lineage malignancies. Here, 1/17 (5.9%, 95% CI: 0.2-28.7%) ALL patients with SMN had CMMRD, which is similar to the 14/189 (7.4%, 95% CI: 4.1-12.1%) paediatric non-Hodgkin lymphoma patients with SMN who had CMMRD in another recent study [14].…”
Section: Mmr Deficiency Hasmentioning
confidence: 99%
“…The 2/19 (10.5%, 95% CI: 1.3-33.1%) relapse samples that were MMR deficient in this study is also consistent with the reported 4-10% frequency. Recently, the TP53 variant c.743G>A (p.R248Q) was found to associate with concurrent MMR deficiency and thiopurine treatment [12], but this variant was [1], and 8/88 (9.1%, 95% CI: 0.4-17.1%) childhood T-LBL patients were diagnosed with CMMRD in a consecutive series between 2007 and 2020 [13], suggesting an association of CMMRD with T cell lineage malignancies. Here, 1/17 (5.9%, 95% CI: 0.2-28.7%) ALL patients with SMN had CMMRD, which is similar to the 14/189 (7.4%, 95% CI: 4.1-12.1%) paediatric non-Hodgkin lymphoma patients with SMN who had CMMRD in another recent study [14].…”
Section: Mmr Deficiency Hasmentioning
confidence: 99%
“…Pathogenic sequence variants that predispose to the manifestation of bone marrow failure and myelodysplastic syndromes, acute myeloid and lymphoblastic leukemias as well as lymphomas, in particular, affect primarily genes whose products contribute to the orderly development and differentiation of the respective tissues, which include various transcription factors, components of various signal transduction pathways and the immune system as well as constituents of the DNA maintenance and repair machinery (8)(9)(10)(11). Most common in the context of lymphoblastic leukemias and lymphomas are thus mutations in the hematopoietic transcription factors ETV6, IKZF1 and PAX5, the tumor suppressor TP53, the DNA mismatch-repair genes MLH1, MSH2, MSH6, and PMS2 as well as ATM, NBN and the RAD51, which are indispensable for the repair of double-strand breaks (8)(9)(10)(12)(13)(14)(15)(16). Amongst those whose dysfunction predisposes primarily to the development of myeloid malignancies are the transcription factors GATA2 and RUNX1, members of the RAS signal transduction and ribosomal protein families, as well as components of the Fanconi and dyskeratosis congenita DNA maintenance and repair system (11,15).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current LBL chemotherapeutic backbone consists of a number of mutagenic agents that can cause additional mutations and contribute to the development of new malignancies in these patients. 2 Additionally, there are indications that MMR deficiency leads to inherent resistance to thiopurines, 8 , 9 , 10 an important component of T‐LBL treatment strategies (LBL2018, NCT04043494). It could therefore be beneficial for CMMRD patients to adapt the LBL backbone by removing the partially toxic and ineffective chemotherapeutic agents and replacing them with other, more effective agents.…”
mentioning
confidence: 99%